Wind power development in Eastern Kazakhstan threatens migration of eagles - Igor V. Karyakin; Elvira G. Nikolenko; Elena P. Shnayder; Ludmila S. Zinevich; Genriyetta I. Pulikova; Natalya G. Andreyenkova; Kordian Bartoszuk; Márton Horváth; Tibor Juhász; Matyas Prommer (Пернатые хищники и их охрана, 2021)
On the basis of data obtained from ARGOS/GPS and GPS/GSM tracking of 34 eagles (4 Steppe Eagles (Aquila nipalensis) from Central KZ, 1 Steppe Eagle from Southern Ural region, 22 Steppe Eagles, 5 Eastern Imperial Eagles (Aquila heliaca) from the ASR and 2 Greater Spotted Eagles (Aquila clanga) from the from the Altai-Sayan Ecoregion), we have defined the main flyways, terms, and other parameters of migration of eagles through Eastern Kazakhstan. We have outlined the borders of the migration corridor and estimate the number of migrants passing through it. The study highlights the importance of the Karatau ridge for eagles from the vast territories ofRussia andKazakhstan. But we are also concerned about the development of wind farms with horizontal-axis wind turbines that expose ultimate danger for raptors in the Karatau migration corridor. One of them already exists – the Zhanatas Wind-Power Station. Here we calculated the possible negative impact on the eagle population from the existing and projected wind farms of the Karatau ridge and give our recommendations for neutralizing the damage from the development of the electric power industry in Karatau.